Art as an interface of law and justice : affirmation, disturbance, disruption - Korsten, Frans-Willem (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This book looks at the way in which the 'call for justice' is portrayed through art and presents a wide range of texts from film to theatre to essays and novels to interrogate the law. The 'call for justice' may have its positive connotations, but throughout history most have caused annoyance. Art is very well suited to deal with such annoyance, or to provoke it. This study shows how art operates as an interface, here, between two spheres: the larger realm of justice and the more specific system of law. This interface has a double potential. It can make law and justice affirm or productively disturb one another. Approaching issues of injustice that are felt globally, eight chapters focus on original works of art not dealt with before, including Milo Rau's The Congo Tribunal, Elfriede Jelinek's Ulrike Maria Stuart, Valeria Luiselli's Tell Me How It Ends and George Eliot's Daniel Deronda. They demonstrate how through art's interface, impasses are addressed, new laws are made imaginable, the span of systems of laws is explored, and the differences in what people consider to be just are brought to light. The book considers the improvement of law and justice to be a global struggle and, whilst the issues dealt with are culture-specific, it argues that the logics introduced are applicable everywhere"--
Art as the interface of law and justice : from annoyance to an ethics of affirmation -- Logic of fear vs logic of desire : Milo Rau's "The Congo tribunal" and the care for law" -- Logic of tragedy vs logic of comedy : Elfriede Jelinek's "Ulrike Maria Stuart and princess-dramas : death and the maiden" -- Logic of the official vs logic of the officious : the force in form and forum in Valeria Luiselli's "Tell me how it ends and lost children archive" -- Logic of personhood vs logic of self : threat of packs in Vondel's 'water-wolf' and the shift of commons into property -- Logic of completion vs logic of antinomy : corruption and well-being from Marek Hasko, to Chibundu Onuzo, to the American suburban grass turf and Fritz Haeg -- Logic of violence vs logic of empathy : justice and law in Chiasmus through George Eliot's "Daniel Deronda" -- Logic of reason vs logic of dream : epistemic authority, habeas corpus, hallucination -- Nicholas Refn's "Only God forgives".
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Law and art; Justice; Law & society; Electronic books